A systematic review of the literature on disorders of sleep and wakefulness in Parkinson's disease from 2005 to 2015. (October 2017) - Chahine, Lama M.; Amara, Amy W.; Videnovic, Aleksandar
Summary: Sleep disorders are among the most common non-motor manifestations in Parkinson's disease (PD) and have a significant negative impact on quality of life. While sleep disorders in PD share most characteristics with those that occur in the general population, there are several considerations specific to this patient population regarding diagnosis, management, and implications. The available research on these disorders is expanding rapidly, but many questions remain unanswered. We thus conducted a systematic review of the literature published from 2005 to 2015 on the following disorders of sleep and wakefulness in PD: REM sleep behavior disorder, insomnia, nocturia, restless legs syndrome and periodic limb movements, sleep disordered breathing, excessive daytime sleepiness, and circadian rhythm disorders. We discuss the epidemiology, etiology, clinical implications, associated features, evaluation measures, and management of these disorders. The influence on sleep of medications used in the treatment of motor and non-motor symptoms of PD is detailed. Additionally, we suggest areas in need of further research.